The Spectrum of the Molecular Eigenstates of Pyrazine and the Reconstruction of Decays of Rotational States of the 1B3u (0–0) Transition of Pyrazine. Issue 3 (1983) - van der Meer, Barend J.; Jonkman, Harry Th.; Kommandeur, Jan
Abstract : The spectrum of the molecular eigenstates (ME) belonging to the various rotational members of the 1 B 3 u (0–0) transition of pyrazine was measured with a very narrow band laser in a molecular beam with a Doppler width of 30 MHz. It is shown that, when the ME's belonging to a single rotational state are Fourier-transformed, the beating decays of these states are obtained. A problem is constituted by the lack of a fast component in these reconstructions, while it is observed in experiments on higher J -states.